Education For Sustainable Development (ESD) climate-based in biology education - Niki Dwi Dia Dara (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2024)
Education for Sustainable Development (ESD) based on climate change in biology learning is an innovative approach to equip students with knowledge, skills, and critical awareness of complex environmental issues. This research discusses the implementation of ESD in the biology curriculum with a focus on climate change, as well as how its integration shapes sustainable attitudes and behaviors in students. Through a literature review, this research identifies effective teaching methods, such as problem-based learning and collaborative learning, which can help students understand the impact of climate change on life and ecosystems. The results obtained indicate that the application of ESD in biology education can enhance students' scientific understanding and critical thinking skills, which are essential for making responsible decisions in the future. The conclusion of this study is that climate change-based ESD is not only relevant for biology education but also important for shaping a more adaptive, responsible generation ready to face global sustainability challenges.